2022
DOI: 10.7860/jcdr/2022/55477.16744
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Lipid Profile with Inflammatory Markers among COVID-19 Positive Patients: A Retrospective Study

Abstract: Introduction: Lipids are fundamental biomolecules of the body. Infections like COVID-19 with intricate immune response in some patient’s leads to acute complications by affecting metabolic pathways at multiple levels. Metabolism of cholesterol, triglyceride and High Density Lipoprotein (HDL)-Cholesterol is deranged by cytokines and multiple inflammatory mediators. The sex differences in lipid metabolism may contribute in susceptibility, severity and outcome of Coronavirus Disease 2019 (COVID-19). Performing li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other research indicates that comorbidities may moderate the relationship between lipid profile and COVID-19 outcomes. For instance, Kumari et al 45 found that lipid profiles may be a potential marker for determining the disease prognosis for COVID-19 patients, but they did not examine the impact of comorbidities. The precise mechanisms coupling these comorbidities to worse outcomes are not fully understood, but they could involve a combination of factors, such as chronic inflammation, impaired immune function, and increased susceptibility to viral entry and replication.…”
Section: Discussionmentioning
confidence: 99%
“…Other research indicates that comorbidities may moderate the relationship between lipid profile and COVID-19 outcomes. For instance, Kumari et al 45 found that lipid profiles may be a potential marker for determining the disease prognosis for COVID-19 patients, but they did not examine the impact of comorbidities. The precise mechanisms coupling these comorbidities to worse outcomes are not fully understood, but they could involve a combination of factors, such as chronic inflammation, impaired immune function, and increased susceptibility to viral entry and replication.…”
Section: Discussionmentioning
confidence: 99%